INFLUENCE OF DREGEA SINENSIS HEMSL. PROTEASE ON THE QUALITY OF MOZZARELLA CHEESE FROM BUFFALO MILK - wang, hongyan; wang, yujing; huang, aixiang (Emirates Journal of Food and Agriculture, 2017)
Dregea sinensis Hemsl. protease, a new enzyme source, is described with the characteristics of milk curd. However, cheese processing with this protease has yet to be described. In this study, a protease called chymosin was extracted and purified from D. sinensis Hemsl. stalk. Calf rennet and microbial chymosin were used as the control group in the production of mozzarella cheese to investigate the effect of this plant species on the quality of cheese. Results: SDS-PAGE revealed that D. sinensis Hemsl. protease can be used to process cheese because this enzyme elicits a degradation effect on α-casein in mozzarella cheese. Fresh and sweet glutamic acid and histidine are the dominant free amino acids in mozzarella cheese (P<0.5). Fifty-two flavor substances were detected through GC-MS. Volatile acids and carbonyl compounds are the main sources of the flavor of mozzarella cheese. Texture profile analysis indicated that the produced cheese was more restorative and flexible. Scanning electron microscopy demonstrated that the produced cheese was smooth, as indicated by the small pore cross-section diameter of mozzarella cheese and its close net structure. Therefore, D. sinensis Hemsl. can be applied to process cheese.